Treatment Effects of Intra-Articular Allogenic Mesenchymal Stem Cell Secretome in an Equine Model of Joint Inflammation - Kearney, Clodagh M.; Khatab, Sohrab; van Buul, Gerben M.; Plomp, Saskia G. M.; Korthagen, Nicoline M.; Labberté, Margot C.; Goodrich, Laurie R.; Kisiday, John D.; Van Weeren, P. R.; van Osch, Gerjo J. V. M.; Brama, Pieter A. J. (Frontiers in Veterinary Science, 2022)
Background: Allogenic Mesenchymal Stem Cell (MSC) secretome is a novel intra-articular therapeutic that has shown promise in in vitro and small animal models and warrants further investigation. Objectives: To investigate if intra-articular allogenic MSC-secretome has anti-inflammatory effects using an equine model of joint inflammation. Study Design: Randomised positively and negatively controlled experimental study. Method: In phase 1 joint inflammation was induced bilaterally in radiocarpal joints of 8 horses by injecting 0.25ng lipopolysaccharide (LPS). Two hours later secretome of INFy and TNFα stimulated allogeneic equine MSCs was injected in one randomly assigned joint, while the contralateral joint was injected with medium (negative control). Clinical parameters (composite welfare scores, joint effusion, joint circumference) were recorded, and synovial fluid samples were analysed for biomarkers (total protein, WBCC; eicosanoid mediators, CCL2; TNF; MMP; GAGs; C2C; CPII) at fixed post-injection hours (PIH 0, 8, 24, 72 and 168 hours). The effects of time and treatment on clinical and synovial fluid parameters and the presence of time–treatment interactions were evaluated. For phase 2, allogeneic MSC-secretome versus allogeneic equine MSCs (positive control) was tested using similar methodology. Results: In phase 1 joint circumference was significantly (p<0.05) lower in the MSC-secretome treated group compared to the medium control group at PIH 24, and significantly higher peak synovial GAG values were noted at PIH 24 (p<0.001). In phase 2, no significant differences were noted between the treatment effects of MSC-secretome and MSCs. Main Limitations: This study is a controlled experimental study and therefore cannot fully reflect natural joint disease. In phase 2, two therapeutics are directly compared and there is no negative control. Conclusions: In this model of joint inflammation, intra-articular MSC-secretome injection had some clinical anti-inflammatory effect. An effect on cartilage metabolism, evident as a rise in GAG levels was also noted, although it is unclear whether this could be considered a beneficial or detrimental effect. When directly comparing MSC-secretome to MSCs in this model results were comparable, indicating that MSC-secretome could be a viable off-the-shelf alternative to MSC treatment.